A3.04 Stromal cell metabolism; the reverse warburg effect in the inflamed synovium. (24th February 2016) - Marshall, JL; Falconer, J; Kapoor, S; Filer, A; Raza, K; Young, SP; Buckley, CD
Abstract : Reprogramming of stromal cell metabolism toward glycolysis in cancerous tissue provides a source of high-energy metabolic intermediates which support proliferation, invasion and metastasis of invading tumour cells; a phenomenon known as the 'Reverse Warburg' effect. We have explored whether a similar interplay may fuel pathogenic processes in autoinflammatory diseases such as rheumatoid arthritis (RA). In RA, fibroblasts are themselves transformed to an aggressive, tumour-like phenotype and also reside in close proximity to energetically demanding immune cells including resident macrophages, infiltrating neutrophils and autoaggressive lymphocytes. We used nuclear magnetic resonance spectroscopy and metabolic flux analysis to identify pathological changes to metabolism in both primary human RA synovial cells, and murine cells from TNF-ΔARE and collagen-induced models of arthritis. We have shown that the fibroblast metabotype correlates with C-reactive protein as a systemic marker of inflammation, and can predict resolution of acute synovitis or progression to chronic RA prior. We have confirmed the clinical prognostic potential of metabolic profiling in inflammatory diseases and demonstrated that synovial fibroblasts increase glycolysis but not mitochondrial respiration in response to inflammatory cues such as tumour necrosis factor-α. Furthermore, analysis of monocarboxylate transporters (MCT-4) supports the likelihood that increased glycolytic products such as lactate may be shuttled between fibroblasts and myeloid cells in situ . Our findings shed light on the metabolic relationships between cells at sites of autoinflammatory pathology and support the therapeutic targeting of the glycolytic pathway beyond oncology. European Union's FP7 Health Programme FP7-HEALTH-F2–2012–305549 AR UK Rheumatoid Arthritis Pathogenesis Centre of Excellence 20298